Islam, Demokrasi, dan HAM Sebuah Benturan Filosofis dan Teologis - Najid Jauhar (Jurnal Ilmu Sosial dan Ilmu Politik, 2007)
Currently, the procedural democracy has been institutionalizing around developing countries whose lslam is major belief. Human rights also become main issues among each Islamic developing country. lslamic value produced historical background of Islamic leadership, the concept of human relation; theological transcendence, individuality, and sociality. Democracy also produced their regulation of power relation, freedom, equality, humanity and sociality. In those democratic countries, human right also produced the practical conceptualization of human right values of individuality and sociality. The philosophical and theological contestntion has been standing different interpretation and belief among lslamic values, democracy and human rights of political actors. This paper will explore the philosophical and theological contestation of Islamic value, democracy and human rights.